The Impact of Tutoring Younger Students on Third Graders' Reading Skills and Perceptions of Themselves as Readers - Wicklund, Rebecca (My University, 2016)
Schools are constantly being pushed to cut budgets and yet have all students be proficient in academic skills. Cross-age tutoring could be a solution because it provides one-on-one interventions that can focus on specific skills that a student struggles with, at a minimal cost, while potentially boosting the tutor’s perception of himself or herself. In this action research project, cross-age tutoring was implemented with a group of third graders as tutors to kindergartners and first graders during breakfast time to determine if there is a change in academic self-esteem and overall reading abilities. The tutors received training in how to deal with situations that may arise and had lessons modeled for them before tutoring the other students. Tutoring was twice a week for fifteen to twenty minutes and the participants who were tutors met five times a week to do reflection and preparation with an instructor. The program lasted eight weeks. Pretests and Posttests were conducted with an additional interview. The results showed little increase in the reading skills given to both the tutors and tutees. However, observation revealed an increase in fluency and ability to apply the reading strategy: Asking Questions. There was also an increase in positive reading attitudes and feelings of self-confidence. Tutors felt that they had been valued and enjoyed working with the younger students. The younger students thoroughly enjoyed being read to and demonstrated an increased desire to read to the tutors. There was an expressed interest from both groups in continuing the tutoring process, though perhaps at a different time and location.